Students' perception of online education during the COVID-19 pandemic - Oana Alexandra Alexa (CES Working Papers, 2021)
Based on the chain of events brought about by the COVID-19 pandemic, 2020 was the year of online education and in many parts of the world, including Romania, this is still the norm in most higher education institutions. After a full academic year of distance learning, 131 undergraduate business students filled in a questionnaire about how they perceived the entire process and what they thought about their Business English course in particular. Results showed that the teaching, learning and evaluation experience was relatively positive, although direct interaction with teachers and peers have suffered the most in the process. Encouragingly, about 43% would like to continue with a hybrid system in the future, which is no doubt due to the flexibility the online system provides. However, further research is needed in terms of establishing the long-term effects of online education on university (language) courses.
Keywords: 330; higher education; students' perception; online education; Business English; pandemic